Therapeutic Gastrointestinal Endoscopy A Comprehensive Atlas - Chun, Hoon Jai; Yang, Suk-Kyun; Choi, Myung-Gyu (Springer Berlin Heidelberg : Imprint: Springer, 2015)
This atlas, featuring a wealth of high-quality images, offers a comprehensive overview of therapeutic gastrointestinal endoscopy for upper and lower gastrointestinal diseases. Both established and new therapeutic techniques using advanced endoscopic devices are extensively covered. The concise text accompanying the endoscopic photographs and illustrations will enable readers to understand the details of each procedure. Special tips of practical value are highlighted and potential pitfalls, identified. The authors are experts in the field who have a great store of knowledge on a wide variety of therapeutic endoscopic procedures. Gastrointestinal endoscopy is the principal tool for the investigation and treatment of most diseases of the gastrointestinal tract. This book will provide the clear guidance that practitioners require in order to perform therapeutic gastrointestinal endoscopy optimally; it will prove indispensable for all gastrointestinal endoscopists.